SOSIALISASI PENGGUNAAN PUPUK ORGANIK CAIR BERBAHAN BAKU GULMA BABANDOTAN PADA KELOMPOK WANITA TANI BANDA LANGIK DI SUNGAI BANGEK KOTA PADANG - Doni Hariandi; Gustian Gustian; Sutoyo Sutoyo; Shalati Febjislami; Afrima Sari; Nugraha Ramadhan (BULETIN ILMIAH NAGARI MEMBANGUN, 2023)
Farmers commonly use inorganic fertilizers such as urea, rock phosphate, and NPK in crop cultivation. Continuous use of these inorganic fertilizers can degrade the quality of the growing medium and increase production costs. Inorganic fertilizers are also relatively expensive. One way to address this issue is by utilizing allelochemical compounds as Liquid Organic Fertilizers (LOF) for plant cultivation. Applying fertilizers in liquid form is more easily absorbed by plants because they are already dissolved and readily available. Babandotan liquid organic fertilizer contains essential nutrients such as nitrogen (N), phosphorus (P), and potassium (K). These elements play a crucial role in stimulating vegetative growth, promoting root development, and strengthening the plant's overall health. The objective of this activity is to enhance the knowledge of the members of the Banda Langik Women Farmers Group about liquid organic fertilizer made from Babandotan weed, as well as to fulfill the Higher Education Tri Dharma for lecturers in the Agrotechnology Program at the Faculty of Agriculture, Andalas University. This community service activity was conducted at the Banda Langik Women Farmers Group, located at Jl. Ekora RT01/RW07 Sungai Bangek, Balai Gadang Village, Koto Tangah District, Padang City, in May-June 2022. The activities performed included preparation, socialization, closing, and reporting. Based on the results of the activity, several key points were identified, including that the community service program was conducted according to the needs of the Women Farmers Group, the group was satisfied and found the service beneficial for their development in the future, and the group members were committed to using LOF in their cultivation areas.